Resolving period aliases for TESS monotransits recovered during the extended mission. Issue 4 (18th November 2020) - Cooke, Benjamin F; Pollacco, Don; Anderson, David R; Bayliss, Daniel; Bouchy, François; Gill, Samuel; Grieves, Nolan; Lendl, Monika; Nielsen, Louise D; Udry, Stéphane; Wheatley, Peter J
ABSTRACT: We set out to explore how best to mitigate the number of period aliases for a transiting Transiting Exoplanet Survey Satellite (TESS) system with two identified transits separated by a large time period on the order of years. We simulate a realistic population of doubly transiting planets based on the observing strategy of the TESS primary and extended missions. We next simulate additional observations using photometry (NGTS) and spectroscopy (HARPS and CORALIE) and assess its impact on the period aliases of systems with two TESS transits. We find that TESS will detect around 400 exoplanets that exhibit one transit in each of the primary and extended missions. Based on the temporal coverage, each of these systems will have an average of 38 period aliases. We find that, assuming a combination of NGTS and CORALIE over observing campaigns spanning 50 d, we can find the true alias, and thus solve the period, for up to 207 of these systems with even more being solved if the observing campaigns are extended or we upgrade to HARPS over CORALIE.